Effect of defaunation on utilisation of poor quality tropical feed by sheep - Teferedegne, B.; Osuji, P.O.; Odenyo, A.A.; Wallace, R.J.; Newbold, C.J. (British Society of Animal Science, 1999)
There are conflicting Reports in the literature about the benefits of defaunation, the removal of ciliate protozoa from the rumen, in ruminant production. Ciliate protozoa are not essential for proper functioning of the rumen nor for the life of the host and that their contribution to microbial protein flowing to the lower gut is small (Williams and Coleman, 1992). Protozoa ingest and digest bacteria in the rumen decreasing the flow of microbial protein from the rumen, and inserting an energy wasting step in the net synthesis of bacterial protein in the rumen (Williams and Coleman, 1992). However, protozoa also play an active role in ruminal fibre digestion and up to 50 percent of ruminal carboxymethylcellulase activity is associated with the protozoal fraction (Williams and Colemans, 1992). Thus the effect of defaunation on animal productivity will be a balance between the increase in the supply of microbial protein leaving the rumen and any decrease in ruminal fibre digestion. The aim of this work was to determine the effect of defaunation on microbial protein supply and fibre digestion in sheep fed a poor quality tropical diet.